1980
DOI: 10.1073/pnas.77.3.1546
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of capacitation: albumin-mediated changes in plasma membrane lipids during in vitro incubation of rat sperm cells.

Abstract: Plasma membrane isolated from rat sperm cells after incubation in vitro had a significantly lower cholesterol/phospholipid mole ratio when the medium contained serum albumin. Transfer of albumin-bound phospholipids to the membrane can largely account for this effect. The result is broadly consistent with a previously proposed model for albumin-induced destabilization of sperm membrane (capacitation) and its reversal by seminal plasma membrane vesicles. Albumin also decreased sialic acid and, more specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(80 citation statements)
references
References 39 publications
4
74
2
Order By: Relevance
“…On the other hand, several studies have provided direct evidence that BSA causes influx of Ca 2+ ions into the plasma membrane [29], decreases the cholesterol and phospholipid ratio in the outer acrosomal membrane of the spermatozoa [30][31][32], and stimulates sperm hyperactivation [33]. BSA is most commonly used as a capacitating agent, and capacitation induces hyperactive motility and 106.3 ± 6.7 C TCG 10 ml 85.6 ± 1.2 66.6 ± 2.0 101.3 ± 6.5 TCG 10 ml + BSA 0.1% 86.0 ± 2.5 65.6 ± 2.1 106.0 ± 5.1 TCG 10 ml + BSA 1% 89.0 ± 0.5 60.6 ± 2.3 95.6 ± 4.0 TCG 10 ml + BSA 5%…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have provided direct evidence that BSA causes influx of Ca 2+ ions into the plasma membrane [29], decreases the cholesterol and phospholipid ratio in the outer acrosomal membrane of the spermatozoa [30][31][32], and stimulates sperm hyperactivation [33]. BSA is most commonly used as a capacitating agent, and capacitation induces hyperactive motility and 106.3 ± 6.7 C TCG 10 ml 85.6 ± 1.2 66.6 ± 2.0 101.3 ± 6.5 TCG 10 ml + BSA 0.1% 86.0 ± 2.5 65.6 ± 2.1 106.0 ± 5.1 TCG 10 ml + BSA 1% 89.0 ± 0.5 60.6 ± 2.3 95.6 ± 4.0 TCG 10 ml + BSA 5%…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of improving sperm freezability by means of a semen collection method. Several researchers have provided direct evidence that BSA, which in extender adheres rapidly to the sperm membrane at the moment of dilution [11], modifies the sperm lipid composition through lipid exchange or hydrolysis [12], promotes plasma membrane protein hydrolysis [13], causes influx of Ca 2+ ions into the cytoplasm [ 1 1 ] , a n d d e c r e a s e s t h e c h o l e s t e r o l a n d phospholipid ratio in the plasma membrane of spermatozoa [14,15]. Moreover, it is well established that cholesterol efflux from the sperm membrane induces enhanced membrane fluidity [16,17], while elevation of membrane cholesterol is associated with decreased membrane fluidity [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed increased cholesterol efflux (50%) in the presence of 5% human female serum or follicular fluid, whereas low cholesterol efflux (14%) was observed in spermatozoa incubated with protein-free medium. In contrast, Davis et al (17) found that cholesterol efflux from sperm membranes was not statistically significant using comparable concentrations of serum albumin. Sugkraroek et al (61) found that using 3.5% human serum albumin (HSA) medium only caused a 5% cholesterol removal from fertile donors' sperm.…”
Section: Miscellaneous Agentsmentioning
confidence: 92%
“…In 1971 Toyoda et al (33) reported successful in vitro fertilization in mice by using a chemically defined medium supplemented with BSA. Later, the role of BSA in capacitation media was tested for mouse, rat, and human sperm capacitation (7,(16)(17)(18)(19)22,34). Likewise, BSA has been used in most media to maintain sperm motility and to promote membrane cholesterol efflux (18)(19)34).…”
Section: Bovine Serum Albuminmentioning
confidence: 99%
See 1 more Smart Citation